CORRECTION OF THE DISORDERS OF THE MOUTH CAVITY BIOCENOSIS AMONG THE CHILDREN WITH CHRONIC TONSILLITIS, AIDED BY THE TOPICAL BACTERIAL LYSATE - E.B. Foshina; V.B. Polishchuk; M.P. Kostinov; L.I. Krasnoproshina ("Paediatrician" Publishers LLC, 2007)
The authors studied the impact of the Imudon bacterial lysate on the status of the tonsil microbiocenosis among the children with chronic tonsillitis in remission. They revealed a certain reduction in the level of pathogenic and opportunistic pathogenic microflora carriage, as well as intensity of the tonsil colonization after 20-day sublingual application of topical bacterial lysate. The medication may be recommended for the preventive practices among the children with chronic tonsillitis to reduce the bacterial contamination of the pharyngeal tonsils.Key words: chronic tonsillitis, children, bacterial lysates, microbiocenosis of the mouth cavity.